The witness experiences of bullying in high school students: A qualitative study [Lise Öğrencilerinin Zorbalığa Tanıklık Yaşantıları: Nitel Bir Araştırma] - (:unkn) unknown (Turkish Psychological Counseling and Guidance Association, 2021)
Bullying is a common problem in today's schools. Bullying affects not only victims and bullies but also the other students who witness the bullying. The purpose of this research is to examine the behaviors shown by high school students who have witnessed bullying and the processes that have led them to these behaviors. By with this purpose, the research benefits from grounded theory design. In-depth interviews have been performed with 36 people who voluntarily participated in the research. The qualitative findings of the research show the witness experience of bullying to be a complex process. As a result of the research, firstly school counselors need to do awareness studies on bullying. Because it is seen that students' definitions of bullying are limited to physical bullying. Secondly, situational conditions seem to change the behavior of individuals who witness bullying. Therefore studies will need to be done directed at school administrators', teachers', and school psychologists' development of positive class climates and formation of anti-bullying norms, as well as at increasing peer relations. Thirdly, this study has demonstrated the importance of cognitive empathy. Cognitive empathy should be added to anti-bullying programs. Research has shown that bullying should be handled as a system that includes teachers, victims, bullies, witnesses, and parents. Copyright © 2021, Author(s).
Keywords: Bullying; Grounded theory; Qualitative design; Witness